2021
DOI: 10.1051/bioconf/20214003002
|View full text |Cite
|
Sign up to set email alerts
|

New drug delivery system in ophthalmology: results studying the surface structure of soft contact lenses from various polymer

Abstract: The development of an ophthalmic therapeutic system includes research on the spatial structure of soft contact lens polymers and the study of the processes of saturation and release of medicinal substances from them. This allows you to determine the methods of saturation of contact lenses with medicinal agents and will open up new opportunities in the treatment of ophthalmological diseases. The purpose of this preliminary fragment of large-scale research was to study the surface structure of soft contact lense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In addition, a study found that pores of different lengths, widths, and depths affect the saturation drug concentration in traditional immersion loading; the difference in drug concentration is the driving force behind drug release in immersion contact lenses; hence, the spatial structure of the contact lens surface will also affect the drug loading and release processes. This indicates that the spatial structure of the contact lens surface is a major area of future research on drug-loaded contact lenses and is worth investigating [14] .…”
Section: Contact Lens Ocular Drug Delivery Systemmentioning
confidence: 99%
“…In addition, a study found that pores of different lengths, widths, and depths affect the saturation drug concentration in traditional immersion loading; the difference in drug concentration is the driving force behind drug release in immersion contact lenses; hence, the spatial structure of the contact lens surface will also affect the drug loading and release processes. This indicates that the spatial structure of the contact lens surface is a major area of future research on drug-loaded contact lenses and is worth investigating [14] .…”
Section: Contact Lens Ocular Drug Delivery Systemmentioning
confidence: 99%